UPAYA PENINGKATKAN MODEL-MODEL PEMBELAJARAN ACTIVE LEARNING PADA GURU MELALUI WORKSHOP DI SDN 20 SUNGAI LIMAU - was, Was (STKIP Pesisir Selatan, 2017)
Based on the observations that researchers have done in SDN 20 Sungai Limau, it was found that teachers' ability in applying learning models is still low. The purpose of this study is to describe and obtain information about the models of instruction applied by the teacher. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 10 teachers of SDN 20 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results showed that the Workshop can improve the ability of teachers in using learning models In SDN 20 Sungai Limau. This is evidenced by the workshop can improve the ability of teachers in using learning models In SDN 20 Sungai Limau from cycle I to cycle II. The average ability of teachers in applying learning models in cycle I is 58.5 with less category, In cycle II is 86.17 Good. Keywords: Workshop, learning models